Evaluación del efecto del selenio sobre la histología muscular en pollos broiler - Masabanda Chimbo, Lucia Rebeca (2025)
In Ecuador, selenium has become a key micronutrient in poultry farming, especially due to the mineral variability present in the grains used as a feed base. Its use, both organic and inorganic, has demonstrated positive effects on meat quality, production efficiency, and intestinal health of broiler chickens by reducing oxidative stress and improving overall bird performance. To evaluate these effects, this research set three specific goals: 1) To analyze the effect of selenium on muscle fiber dimensions in broiler chickens, 2) To identify the effect of selenium supplementation on production parameters, and 3) To determine the benefit/cost ratio of the evaluated diets. The study was carried out in the poultry house of Mr. William Verdezoto, located in the Las Palmas sector, Chimbo- Guaranda road, using a Randomized Complete Block Design (RCBD) with three treatments, two based on the administration of selenium in their feed and a control treatment. The results showed that the treatment with 300 g/ton of selenium (T1) allowed to reach the highest average weight at the sixth week (1965.3 g) and a feed conversion (1.80), indicating feed efficiency. The histological analysis revealed that selenium did not significantly influence the width of the muscle fibers, but it did present changes in the area and significantly reduced their length, reason why the alternative hypothesis is accepted. Regarding the economic analysis, treatment 3 obtained the highest benefit/cost ratio with (0.55) meaning that for every dollar invested, 55 cents were recovered.